Estructuras productivas y desarrollo: El caso de la economía chilena; Productive structures and development: The case of the Chilean economy - Sergio Soza-Amigo; Patricio Aroca (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– This research begins with the following questions: Is there consistency between the identification of development and the economic structure that is possessed?; are there similarities among economies identified with differences in their levels of development?; and, are there non-developed economies with the same structure as that of developed economies? To answer these questions, similarities of input-output tables obtained from OECD (Mid90, Early00 and Mid00) are reviewed and then, a case study is performed on the Chilean economy. The similarities and changes are investigated by using a structural similarity index, and then by comparing correlations. The results show that: Traditional indicators can only be used as references and are non-categorical in their identification of development; the economies show significant similarities according to their level of development; and there exists significant structural similarities between developed economies and the economy of Chile.
Keywords: C49; C67; D57; F02; R11; 330; Input-output analysis; linkage; structural change